A two-phase model of solid tumour growth - Byrne, H; King, JR; MCElwain, D; Preziosi, L (2003)
Many solid tumour growth models are formulated as systems of parabolic and/or hyperbolic equations. Here an alternative, two-phase theory is developed to describe solid tumour growth. Versions of earlier models are recovered when suitable limits of the new model are taken. We contend that the multiphase approach represents a more general, and natural, modelling framework for studying solid tumour growth than existing theories. © 2003 Elsevier Science Ltd. All rights reserved.